Preparation method of fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair and hydrogel composite material
By preparing fat glue/micro-nano bioglass/GelMA photocured hydrogel composites, combined with blue light-induced crosslinking method, the problems of uneven coverage of fat glue on the wound surface and sustained release of growth factors in the prior art were solved, and the wound healing rate was significantly improved and the continuous release of growth factors were achieved.
Patent Information
- Application Number
- CN202411895436.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the direct application of fat glue cannot be uniformly covered on the wound surface, lacks adhesion and large fluidity, resulting in loss and waste, and the sustained release of growth factors cannot be achieved, resulting in short retention time in the body.
A hydrogel that can promote wound repair was prepared by using fat gel/micro-nano bioglass/GelMA photocured hydrogel composite material.
The hydrogel has stable rheology and slow biodegradability, which can achieve continuous release of growth factors, significantly improve the wound healing rate, and overcome the problems of short retention period and prone to inactivation of fat gels in the body.
Smart Images

Figure CN119857174A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical biomaterials, and in particular to a preparation method of a fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair and a hydrogel composite material. Background Art
[0002] Fat gel is a concentrated fat product obtained by physical methods. It is rich in stromal vascular fraction (SVF) and extracellular matrix (ECM). Fat gel plays an important role in wound healing. It not only promotes angiogenesis, but also contains many proteins and growth factors. Fat gel is separated from fat and contains a large number of various growth factors, such as platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor-β (TGF-β) and epidermal growth factor (EGF), which all contribute to wound repair. In addition, biomaterials loaded with fat gel can stimulate the proliferation and differentiation of fibroblasts, reduce the secretion of proteolytic matrix metalloproteinases (MMPs), and provide an ideal microenvironment for wound healing.
[0003] However, the current fat glue management method has several disadvantages. For example, directly applying fat glue cannot evenly cover the wound surface. Fat glue does not have adhesion to the skin and has high fluidity. Direct application on the wound surface will cause the loss and waste of fat glue, and it cannot play a sustained-release role; it is retained in the body for a very short time. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a preparation method of a fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material and a hydrogel composite material for promoting wound repair.
[0005] The method of the present invention is achieved by adopting the following technical solutions:
[0006] A method for preparing a fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair, comprising the following steps:
[0007] S1. Preparation of methacrylated gelatin (GelMA)
[0008] S1a. 10 g of gelatin was completely dissolved in 500 mL of PBS solution at 60° C. to obtain a mixture, and then 10 mL of methacrylic anhydride (MA) was added to the mixture at 50° C. to react for 8 hours until it turned milky white;
[0009] S1b. The mixture in step S1a was placed in a membrane with a molecular weight cutoff of 7000Da and dialyzed at 40°C for 1 week to remove unreacted methacrylic anhydride and other by-products;
[0010] S1c. The product in step S1b was placed in a -80°C refrigerator and frozen for 30 min, and then the sample was freeze-dried for 24 hours to obtain GelMA, and stored at -20°C for further use;
[0011] S2. Preparation of radial mesoporous bioactive glass nanospheres (HCa-MBG)
[0012] S2a. 0.6 g of urea was dissolved in 30 ml of deionized water, and 1 g of hexadecylic trimethyl ammonium bromide (CTAB), 30 ml of cyclohexane, 0.92 g of isopropanol, and 2.7 mL of ethyl orthosilicate were added thereto. After stirring for 30 min, the temperature was raised to 70 ° C. After stirring for 1 h, a complete solution was obtained.
[0013] S2b. 0.708 g of calcium nitrate tetrahydrate was added to the mixture solution in step S2a, heated and stirred for 16 hours, and then cooled to room temperature.
[0014] S2c the mixture of step S2b at 10000r / min or more centrifugation speed for 15 minutes, remove the solution, and then washed three times with ethanol and deionized water, and finally freeze-dried or dried;
[0015] S2d. The product of step S2c was heated at a rate of 1°C / min and kept at 600°C for 5h to obtain HCa-MBG;
[0016] S3. Preparation of fat gel
[0017] S3a. Use a 4mm diameter multi-side hole liposuction needle to suck fat from the patient's abdomen or thigh at an air pressure of -0.75atm, centrifuge the harvested fat at 1200g / min for 3min, remove the blood and swelling fluid at the bottom after centrifugation, and obtain Coleman fat. According to the amount of fat, the upper layer of Coleman fat with more fat is marked as low-density fat, and the lower layer of Coleman fat with less fat is marked as high-density fat;
[0018] S3b. The low-density Coleman fat after centrifugation in step S3a is transferred to a 10 mL syringe, which is connected to another 10 mL syringe via a 2.4 mm Luer connector, and the injection rate is 10 mL / sec, and the injection is repeated to emulsify the low-density Coleman fat to obtain nano fat;
[0019] S3c. The nano fat obtained in step S3b was centrifuged at 1600g / min for 3min and was divided into three layers after centrifugation, the upper layer of fat and the lowermost liquid portion, and the gel-like product in the middle layer was SVF-gel;
[0020] S3d. The appropriate amount of upper fat after centrifugation in step S3c was poured into the remaining untreated high-density Coleman fat in step S3a, and steps S3b and S3c were repeated to obtain another portion of SVF-gel;
[0021] S4. Preparation of fat gel / micro-nano bioglass / GelMA photocurable hydrogel for wound repair
[0022] S4a. Dissolve methacrylated gelatin and photoinitiator in deionized water at 65°C and mix thoroughly;
[0023] S4b. Add fat gel and bioglass to the mixture obtained in step S4a, and irradiate with blue light for 5 to 10 seconds to obtain fat gel / micro-nano bioglass / GelMA photocurable hydrogel that promotes wound repair.
[0024] Furthermore, in step S1b, unreacted impurities are removed by centrifugation at 5500 pm.
[0025] Furthermore, in step S1b, the molecular weight cutoff of the cutoff membrane is 7000-15000Da.
[0026] Furthermore, in step S2d, HCa-MBG is obtained after the insulation time is about 5 hours.
[0027] Furthermore, in step S3b, the Coleman fat is emulsified and appears as yellow flocs.
[0028] Furthermore, in step S4a, the configuration ratio of the GelMA solution is 1 ml PBS is added to 0.1 g GelMA to obtain the GelMA solution.
[0029] Furthermore, in step S4a, the GelMA solution is prepared and dissolved in a water bath at 40°C-60°C.
[0030] Furthermore, in step S4a, the photoinitiator solution is prepared by adding 500 uL of anhydrous ethanol to 15 mg of the photoinitiator to obtain the photoinitiator solution.
[0031] Furthermore, in step S4a, the photoinitiator solution is added in a ratio of 100 uL of the photoinitiator solution to 1 mL of the GelMA solution.
[0032] Furthermore, in step S4b, the configuration ratio of HCa-MBG to GelMA is 0.0625 g HCa-MBG added to 2.5 mL GelMA.
[0033] Furthermore, in step S4b, SVF-gel can be prepared according to different concentrations, and generally, 5%-10% SVF-gel has the best effect.
[0034] The present invention also provides a hydrogel composite material made by the above method, which is prepared by a blue light induced cross-linking method. The fat gel and micro-nano bioglass that promote wound repair can promote the release of vascular endothelial growth factor (VEGF) and other cytokines in damaged tissues, promote the regeneration of blood vessels and collagen, and achieve the slow release of growth factors in the fat gel in the hydrogel, which is applied to chronic difficult-to-heal wounds.
[0035] The present invention has the following beneficial effects:
[0036] 1) The hydrogel provided by the present invention has stable rheological properties, slow biodegradability and good mechanical properties.
[0037] 2) The hydrogel provided by the present invention has an excellent sustained release effect on the growth factors in the fat gel and the bioglass, and the sustained release rate of the growth factors can reach 14 days.
[0038] 3) The hydrogel provided by the present invention is a natural hydrophilic colloid with good adhesion and biocompatibility. Methacrylated gelatin (GelMA) is the main material of the carrier and is an ideal photo-crosslinked skin dressing that can mimic the structure of the extracellular matrix (ECM). However, traditional gelatin materials have no biological activity, which limits their use. In addition, the hydrogel of the present invention has a connected reticular space, which can achieve the controlled release of growth factors and bioglass, and is an ideal carrier for tissue engineering applications.
[0039] 4) The present invention adopts a blue light-induced cross-linking method to prepare a fat gel / micro-nano bioglass / GelMA photocurable hydrogel that promotes wound repair, which can promote the release of vascular endothelial growth factor (VEGF) and other cytokines in damaged tissues, thereby promoting the regeneration of blood vessels and collagen; and also realizes the slow release of growth factors in the fat gel in the hydrogel, overcoming the problems of short retention period and easy inactivation of growth factors in the current fat gel. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in multiple embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0041] Figure 1 It is a schematic diagram of the structure of the micro-nano bioglass of the present invention;
[0042] Figure 2 Schematic diagram of the structure of the methacrylated hydrogel (GelMA) of the present invention;
[0043] Figure 3 The SVF-gel prepared according to the present invention;
[0044] Figure 4 This is a schematic diagram of the fat glue / micro-nano bioglass / GelMA light-cured hydrogel for promoting wound repair of the present invention;
[0045] Figure 5 Schematic diagram of the effects of various hydrogels of the present invention on cell migration;
[0046] Figure 6 It is a schematic diagram of the effects of various hydrogels of the present invention on animal wound surfaces. DETAILED DESCRIPTION
[0047] The invention is further described below with reference to the accompanying drawings and embodiments.
[0048] Example 1
[0049] S1. Preparation of methacrylated gelatin (GelMA)
[0050] S1a. Dissolve 10 g of gelatin particles in 500 mL of PBS solution (pH = 7.4) and stir at a constant temperature of 50°C using a magnetic stirrer. After it is fully dissolved, add 10 mL of methacrylic anhydride solution slowly and evenly using a micropump and allow it to react completely with the gelatin for 4 hours;
[0051] S1b. The mixture in step S1a was placed in a membrane with a molecular weight cutoff of 7000Da and dialyzed at 40°C for 1 week to remove unreacted methacrylic anhydride and other by-products;
[0052] S1c. The product in step S1b was placed in a -80°C refrigerator and frozen for 30 min, and then the sample was freeze-dried for 24 hours to obtain GelMA, and stored at -20°C for further use;
[0053] S2. Preparation of radial mesoporous bioactive glass nanospheres (HCa-MBG)
[0054] S2a. 0.6 g of urea was dissolved in 30 ml of deionized water, and 1 g of hexadecylic trimethyl ammonium bromide (CTAB), 30 ml of cyclohexane, 0.92 g of isopropanol, and 2.7 mL of ethyl orthosilicate were added thereto. After stirring for 30 min, the temperature was raised to 70 ° C. After stirring for 1 h, a complete solution was obtained.
[0055] S2b. 0.708 g of calcium nitrate tetrahydrate was added to the mixture solution in step S2a, heated and stirred for 16 hours, and then cooled to room temperature.
[0056] S2c the mixture of step S2b at 10000r / min or more centrifugation speed for 15 minutes, remove the solution, and then washed three times with ethanol and deionized water, and finally freeze-dried or dried;
[0057] S2d. The product of step S2c was heated at a rate of 1°C / min and kept at 600°C for 5h to obtain HCa-MBG;
[0058] S3. Preparation of fat gel
[0059] S3a. Use a 4mm diameter multi-side hole liposuction needle to suck fat from the patient's abdomen or thigh at an air pressure of -0.75atm, centrifuge the harvested fat at 1200g / min for 3min, remove the blood and swelling fluid at the bottom after centrifugation, and obtain Coleman fat. According to the amount of fat, the upper layer of Coleman fat with more fat is marked as low-density fat, and the lower layer of Coleman fat with less fat is marked as high-density fat;
[0060] S3b. The low-density Coleman fat after centrifugation in step S3a is transferred to a 10 mL syringe, which is connected to another 10 mL syringe via a 2.4 mm Luer connector, and the injection rate is 10 mL / sec, and the injection is repeated to emulsify the low-density Coleman fat to obtain nano fat;
[0061] S3c. The nano fat obtained in step S3b was centrifuged at 1600g / min for 3min and was divided into three layers after centrifugation, the upper layer of fat and the lowermost liquid portion, and the gel-like product in the middle layer was SVF-gel;
[0062] S3d. The appropriate amount of upper fat after centrifugation in step S3c was poured into the remaining untreated high-density Coleman fat in step S3a, and steps S3b and S3c were repeated to obtain another portion of SVF-gel;
[0063] S4. Preparation of fat gel / micro-nano bioglass / GelMA photocurable hydrogel for wound repair
[0064] S4a. Dissolve methacrylated gelatin and photoinitiator in deionized water at 65°C and mix thoroughly;
[0065] S4b. Add fat gel and bioglass to the mixture obtained in step S4a, and irradiate with blue light for 5 to 10 seconds to obtain fat gel / micro-nano bioglass / GelMA photocurable hydrogel that promotes wound repair.
[0066] The fat gel / micro-nano bioglass / GelMA light-cured hydrogel prepared above for promoting wound repair can be used for the treatment of chronic wounds and the repair of soft tissue injuries, and can be directly covered on the wound surface through a syringe and solidified by light.
[0067] Example 2
[0068] S1. Preparation of methacrylated gelatin (GelMA)
[0069] S1a. Dissolve 10 g of gelatin particles in 500 mL of PBS solution (pH = 7.4) and stir at a constant speed with a magnetic stirrer at a constant temperature of 50°C. After it is fully dissolved, add 10 mL of methacrylic anhydride solution slowly and evenly with a micropump and let it react completely with the gelatin for 4 hours until it turns milky white;
[0070] S1b. The mixture in step S1a was placed in a membrane with a molecular weight cutoff of 10,000 Da and dialyzed at 40 ° C for 1 week to remove unreacted methacrylic anhydride and other by-products;
[0071] S1c. The product in step S1b was placed in a -80°C refrigerator and frozen for 40 min, and then the sample was freeze-dried for 24 hours to obtain GelMA, and stored at -20°C for further use;
[0072] S2. Preparation of radial mesoporous bioactive glass nanospheres (HCa-MBG)
[0073] S2a. 0.6 g of urea was dissolved in 30 ml of deionized water, and 1 g of hexadecylic trimethyl ammonium bromide (CTAB), 30 ml of cyclohexane, 0.92 g of isopropanol, and 2.7 mL of ethyl orthosilicate were added thereto. After stirring for 30 min, the temperature was raised to 70 ° C. After stirring for 1 h, a complete solution was obtained.
[0074] S2b. 0.708 g of calcium nitrate tetrahydrate was added to the mixture solution in step S2a, heated and stirred for 16 hours, and then cooled to room temperature.
[0075] S2c the mixture of step S2b at 10000r / min or more centrifugation speed for 15 minutes, remove the solution, and then washed three times with ethanol and deionized water, and finally freeze-dried or dried;
[0076] S2d. The product of step S2c was heated at a rate of 1°C / min and kept at 600°C for 5h to obtain HCa-MBG;
[0077] S3. Preparation of fat gel
[0078] S3a. Use a 4mm diameter multi-side hole liposuction needle to suck fat from the patient's abdomen or thigh at an air pressure of -0.75atm, centrifuge the harvested fat at 1400g / min for 3min, remove the blood and swelling fluid at the bottom after centrifugation, and obtain Coleman fat. According to the amount of fat, the upper layer of Coleman fat with more fat is marked as low-density fat, and the lower layer of Coleman fat with less fat is marked as high-density fat;
[0079] S3b. The low-density Coleman fat after centrifugation in step S3a is transferred to a 10 mL syringe, which is connected to another 10 mL syringe via a 2.4 mm Luer connector, and the injection rate is 10 mL / sec, and the injection is repeated to emulsify the low-density Coleman fat to obtain nano fat;
[0080] S3c. The nano fat obtained in step S3b was centrifuged at 1800g / min for 3min and divided into three layers after centrifugation, the upper layer of fat and the lowermost liquid portion, and the gel-like product in the middle layer was SVF-gel;
[0081] S3d. The appropriate amount of upper fat after centrifugation in step S3c was poured into the remaining untreated high-density Coleman fat in step S3a, and steps S3b and S3c were repeated to obtain another portion of SVF-gel;
[0082] S4. Preparation of fat gel / micro-nano bioglass / GelMA photocurable hydrogel for wound repair
[0083] S4a. Dissolve methacrylated gelatin and photoinitiator in deionized water at 65°C and mix thoroughly;
[0084] S4b. Add fat gel and bioglass to the mixture obtained in step S4a, and irradiate with blue light for 20 seconds to obtain fat gel / micro-nano bioglass / GelMA photocurable hydrogel that promotes wound repair.
[0085] The fat gel / micro-nano bioglass / GelMA light-cured hydrogel prepared above for promoting wound repair can be used for the treatment of chronic wounds and the repair of soft tissue injuries, and can be directly covered on the wound surface through a syringe and solidified by light.
[0086] Example 3
[0087] S1. Preparation of methacrylated gelatin (GelMA)
[0088] S1a. Dissolve 10 g of gelatin particles in 500 mL of PBS solution (pH = 7.4) and stir at a constant speed with a magnetic stirrer at a constant temperature of 50°C. After it is fully dissolved, add 10 mL of methacrylic anhydride solution slowly and evenly with a micropump and let it react completely with the gelatin for 4 hours until it turns milky white;
[0089] S1b. The mixture in step S1a was placed in a membrane with a molecular weight cutoff of 12000Da and dialyzed at 40°C for 1 week to remove unreacted methacrylic anhydride and other by-products;
[0090] S1c. The product in step S1b was placed in a -80°C refrigerator and frozen for 35 min, and then the sample was freeze-dried for 24 hours to obtain GelMA, and stored at -20°C for further use;
[0091] S2. Preparation of radial mesoporous bioactive glass nanospheres (HCa-MBG)
[0092] S2a. 0.6 g of urea was dissolved in 30 ml of deionized water, and 1 g of hexadecylic trimethyl ammonium bromide (CTAB), 30 ml of cyclohexane, 0.92 g of isopropanol, and 2.7 mL of ethyl orthosilicate were added thereto. After stirring for 30 min, the temperature was raised to 70 ° C. After stirring for 1 h, a complete solution was obtained.
[0093] S2b. 0.708 g of calcium nitrate tetrahydrate was added to the mixture solution in step S2a, heated and stirred for 16 hours, and then cooled to room temperature.
[0094] S2c the mixture of step S2b at 10000r / min or more centrifugation speed for 15 minutes, remove the solution, and then washed three times with ethanol and deionized water, and finally freeze-dried or dried;
[0095] S2d. The product of step S2c was heated at a rate of 1°C / min and kept at 600°C for 5h to obtain HCa-MBG;
[0096] S3. Preparation of fat gel
[0097] S3a. Use a 4mm-caliber multi-side hole liposuction needle to suck fat from the patient's abdomen or thigh at an air pressure of -0.75atm, centrifuge the harvested fat at 1300g / min for 3min, remove the blood and swelling fluid at the bottom after centrifugation, and obtain Coleman fat. According to the amount of fat, the upper layer of Coleman fat with more fat is marked as low-density fat, and the lower layer of Coleman fat with less fat is marked as high-density fat;
[0098] S3b. The low-density Coleman fat after centrifugation in step S3a is transferred to a 10 mL syringe, which is connected to another 10 mL syringe via a 2.4 mm Luer connector, and the injection rate is 10 mL / sec, and the injection is repeated to emulsify the low-density Coleman fat to obtain nano fat;
[0099] S3c. The nano fat obtained in step S3b was centrifuged at 1700g / min for 3min and was divided into three layers after centrifugation, the upper layer of fat and the lowermost liquid portion, and the gel-like product in the middle layer was SVF-gel;
[0100] S3d. The appropriate amount of upper fat after centrifugation in step S3c was poured into the remaining untreated high-density Coleman fat in step S3a, and steps S3b and S3c were repeated to obtain another portion of SVF-gel;
[0101] S4. Preparation of fat gel / micro-nano bioglass / GelMA photocurable hydrogel for wound repair
[0102] S4a. Dissolve methacrylated gelatin and photoinitiator in deionized water at 65°C and mix thoroughly;
[0103] S4b. Add fat gel and bioglass to the mixture obtained in step S4a, and irradiate with blue light for 5 to 10 seconds to obtain fat gel / micro-nano bioglass / GelMA photocurable hydrogel that promotes wound repair.
[0104] The fat gel / micro-nano bioglass / GelMA light-cured hydrogel prepared above for promoting wound repair can be used for the treatment of chronic wounds and the repair of soft tissue injuries, and can be directly covered on the wound surface through a syringe and solidified by light.
[0105] The following is a further experimental test on the fat gel / micro-nano bioglass / GelMA photocurable hydrogel for promoting wound repair prepared in the above example.
[0106] (1) The effects of fat gel / micro-nano bioglass / GelMA photocurable hydrogel on cell migration that promotes wound repair.
[0107] Experimental methods:
[0108] HDF cells and HUVEC cells were seeded into 6-well plates and cultured until they reached more than 80% confluence, and then randomly divided into eight groups. They were cultured in 100% concentration of GelMA 24h serum-free DMEM extract, GelMA / SVF-gel 24h serum-free DMEM extract, GelMA / HCa-MBG 24h serum-free DMEM extract, and GelMA / SVF-gel / HCa-MBG 24h serum-free DMEM extract, and images were taken at different time periods.
[0109] Experimental results and conclusions
[0110] The experimental results are as follows Figure 5 As shown, after co-culture with 100% concentration extract, HDF cells cultured in GelMA / SVF-gel extract showed the highest migration rate, which was better than that of GelMA / SVF-gel / HCa-MBG extract group. This proves that SVF-gel has a significant repair effect, and the addition of HCa-MBG will reduce the migration speed, which has a good inhibitory effect on scar formation in the late stage of wound healing.
[0111] (2) The effects of fat gel / micro-nano bioglass / GelMA photocuring hydrogel on animal wounds that promote wound repair.
[0112] Experimental methods:
[0113] Remove the hair on both sides of the rat's back, mark the size of the model with a radius of 0.9 cm, and disinfect the skin with 75% alcohol. Under a sterile environment, accurately cut the skin and subcutaneous tissue along the marked line until the fascia layer. Figure 6GelMA, GelMA / SVF-gel (2.5%, 5%, 10%, 20%, 40%), GelMA / HCa-MBG, and GelMA / SVF-gel / HCa-MBG were prepared and applied to the wound surface. We took photos on the 3rd, 7th, 14th, and 21st days to evaluate the wound area and calculate the wound closure rate.
[0114] Experimental results and conclusions
[0115] The experimental results are as follows Figure 6 As shown in the figure, the healing rate of the GelMA / SVF-gel / HCa-MBG group reached an astonishing 85.1±3.4% on the 7th day, while the healing rates of the other three groups were only 71±3.8%, 58±0.6% and 73.3±6.3%, respectively. This shows that the healing rate of the GelMA / SVF-gel / HCa-MBG group was significantly higher than that of the other three groups. Figure 4 and Figure 5 The data showed that the healing rate of the GelMA group reached 95.3±4.9%, while the healing rate of the GelMA / SVF-gel / HCa-MBG group reached 99.2±0.5%, indicating that the difference between the two groups was statistically significant (P<0.05). This shows that GelMA / SVF-gel / HCa-MBG and GelMA / SVF-gel can increase the speed of early epithelialization and the thickness of the epithelium of the wound, and promote the regeneration of blood vessels on the wound surface.
[0116] The embodiments of the specific method are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, it is obvious to those skilled in the art that the technical solution of the present invention may be modified and varied. Any modification or equivalent substitution made within the spirit and principles of the present application shall be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a fat gel / micro-nano bioglass / GelMA photocurable hydrogel for promoting wound repair, characterized in that: The following steps are involved: S1. Preparation of methacrylated gelatin (GelMA) S1a. 10 g of gelatin was completely dissolved in 500 mL of PBS solution at 60° C. to obtain a mixture, and then 10 mL of methacrylic anhydride (MA) was added to the mixture at 50° C. to react for 8 hours until it turned milky white; S1b. The mixture in step S1a was placed in a membrane with a molecular weight cutoff of 7000Da and dialyzed at 40°C for 1 week to remove unreacted methacrylic anhydride and other by-products; S1c. The product in step S1b was placed in a -80°C refrigerator and frozen for 30 min, and then the sample was freeze-dried for 24 hours to obtain GelMA, and stored at -20°C for further use; S2. Preparation of radial mesoporous bioactive glass nanospheres (HCa-MBG) S2a. 0.6 g of urea was dissolved in 30 ml of deionized water, and 1 g of hexadeciyltrimethylammonium bromide (CTAB), 30 ml of cyclohexane, 0.92 g of isopropanol, and 2.7 mL of tetraethyl orthosilicate were added thereto. After stirring for 30 min, the temperature was raised to 70 ° C. After stirring for 1 h, a complete solution was obtained. S2b was added to the mixture solution in step S2a 0.708g of calcium nitrate tetrahydrate, heated and stirred for 16 hours, and then cooled to room temperature; S2c the mixture of step S2b at 10000r / min or more centrifugation speed for 15 minutes, remove the solution, and then washed three times with ethanol and deionized water, and finally freeze-dried or dried; S2d. The product of step S2c was heated at a rate of 1°C / min and kept at 600°C for 5h to obtain HCa-MBG; S3. Preparation of fat gel S3a. Use a 4mm diameter multi-side hole liposuction needle to suck fat from the patient's abdomen or thigh at an air pressure of -0.75atm, centrifuge the harvested fat at 1200g / min for 3min, remove the blood and swelling fluid at the bottom after centrifugation, and obtain Coleman fat. According to the amount of fat, the upper layer of Coleman fat with more fat is marked as low-density fat, and the lower layer of Coleman fat with less fat is marked as high-density fat; S3b. The low-density Coleman fat after centrifugation in step S3a is transferred to a 10 mL syringe, which is connected to another 10 mL syringe via a 2.4 mm Luer connector, and the injection rate is 10 mL / sec, and the injection is repeated to emulsify the low-density Coleman fat to obtain nano fat; S3c. The nano fat obtained in step S3b was centrifuged at 1600g / min for 3min and was divided into three layers after centrifugation, the upper layer of fat and the lowermost liquid portion, and the gel-like product in the middle layer was SVF-gel; S3d. The appropriate amount of upper fat after centrifugation in step S3c was poured into the remaining untreated high-density Coleman fat in step S3a, and steps S3b and S3c were repeated to obtain another portion of SVF-gel; S4. Preparation of fat gel / micro-nano bioglass / GelMA photocurable hydrogel for wound repair S4a. Dissolve methacrylated gelatin and photoinitiator in deionized water at 65°C and mix thoroughly; S4b. Add fat gel and bioglass to the mixture obtained in step S4a, and irradiate with blue light for 5 to 10 seconds to obtain fat gel / micro-nano bioglass / GelMA photocurable hydrogel that promotes wound repair.
2. The method for preparing the fat glue / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S1b, unreacted impurities are removed by centrifugation at 5500 pm.
3. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S1b, the molecular weight cut-off of the cut-off membrane is 7000-15000 Da.
4. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S2d, HCa-MBG is obtained after the heat preservation time is about 5 hours.
5. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S3b, Coleman's fat is emulsified and appears as yellow floccules.
6. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S4a, the configuration ratio of the GelMA solution is 1 ml of PBS added to 0.1 g of GelMA to obtain the GelMA solution.
7. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S4a, the GelMA solution is prepared and dissolved in a water bath at 40°C-60°C.
8. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S4a, the photoinitiator solution is prepared by adding 500 uL of anhydrous ethanol to 15 mg of photoinitiator to obtain a photoinitiator solution.
9. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S4a, the photoinitiator solution is added in a ratio of 100 uL of the photoinitiator solution to 1 mL of the GelMA solution.
10. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S4b, the configuration ratio of HCa-MBG to GelMA is 0.0625 g HCa-MBG added to 2.5 mL GelMA.
11. The method for preparing the fat gel / micro-nano bioglass / GelMA light-cured hydrogel composite material for promoting wound repair according to claim 1, characterized in that: In step S4b, the concentration of SVF-gel is 5%-10%.
12. The hydrogel composite material prepared by the method according to any one of claims 1 to 11, characterized in that: The hydrogel composite material is prepared by a blue light-induced cross-linking method, and the fat gel and micro-nano bioglass that promote wound repair promote the release of vascular endothelial growth factor (VEGF) and other cytokines in damaged tissues, promote the regeneration of blood vessels and collagen, and achieve the slow release of growth factors in the fat gel in the hydrogel, and is applied to chronic difficult-to-heal wounds.